Evo, Pablo, Tony, Diego, and Sonny : General Equilibrium Analysis of the Illegal Drugs Market - Chumacero, Rómulo A. (The World Bank, 2008)
This paper presents a general equilibrium model for the production, trafficking, and consumption of illegal drugs which endogenously determines relative prices and quantities. The model is calibrated to characterize the market for cocaine and is used to analyze the effects of three types of policies: making the illegal activities riskier, increasing the penalties for conducting illegal activities, and legalizing previously illegal activities. Assessing the effects of these policies using the powerful tool of a general equilibrium model provides illuminating (and in cases surprising) results